'Have you heard that young people are RECLAIMing their future?': Towards a bold, ethical and hopeful politics of Brexit and beyond. (May 2017) - Future, Team; Pottinger, Laura; Hall, Sarah Marie
In this paper, co-authored with young people from Team Future, a youth-led campaign associated with Manchester charity RECLAIM, we provide insights into the recent EU referendum result in the UK and the process of decision-making according to young people. Reports following the vote for Brexit largely focused on the intergenerational differences in voting and the (distributional) injustices enacted by current generations in voting against the will of future generations. However, we argue that there were other forms of injustice at work. We start with the case for critiquing the referendum not only according to the outcome but also as a process, as an example of procedural injustice. We then go on to explore the purpose of Team Future for addressing this injustice, a campaign focused on political education for all and of a bold, ethical and hopeful politics of Brexit and beyond.